Pressure sensitive organic sensor based on CNT-VO2 (3fl) composite - Adam Khan,; Karimov, Kh. S.; Khaulah Sulaiman,; Mutabar Shah,; Moiz, S.A. (Universiti Kebangsaan Malaysia, 2014)
In this paper, fabrication and investigation of organic pressure sensor based on Al/CNT-VO2 (3fl)/Cu composite is reported. The active layer of the composite was deposited by drop-casting of the blend CNT-VO2 (3fl) on a glass substrate (with prefabricated copper (Cu) electrode). The thin film of the blend consists of carbon nanotube CNT, (2.55 wt. %) and vanadium oxide (VO2 (3fl)) micropowder, (3 wt. %) in benzol (1 mL). The thickness of the composite was in the range of 20-40 μm. It was found that the fabricated sensor was sensitive to pressure and showed good repeatability. The decrease in resistance of the sensor was observed by increasing the external uniaxial pressure up to 50 kNm-2. The experimentally obtained results were compared with the simulated results and showed reasonable agreement with each other.